2013
DOI: 10.1371/journal.pone.0076120
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing Reveals Differential Expression of miRNAs in Intestine from Sea Cucumber during Aestivation

Abstract: The regulatory role of miRNA in gene expression is an emerging hot new topic in the control of hypometabolism. Sea cucumber aestivation is a complicated physiological process that includes obvious hypometabolism as evidenced by a decrease in the rates of oxygen consumption and ammonia nitrogen excretion, as well as a serious degeneration of the intestine into a very tiny filament. To determine whether miRNAs play regulatory roles in this process, the present study analyzed profiles of miRNA expression in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 40 publications
(43 reference statements)
4
55
0
Order By: Relevance
“…This is consistent with the observation based on the systematic analysis of thousands of metazoan miRNAs [28]. In canonical cases, the 2 nd to the 8 th nucleotides of miRNAs, named as “seed region”, are perfectly complementary with their target sites.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the observation based on the systematic analysis of thousands of metazoan miRNAs [28]. In canonical cases, the 2 nd to the 8 th nucleotides of miRNAs, named as “seed region”, are perfectly complementary with their target sites.…”
Section: Discussionsupporting
confidence: 90%
“…One of the reasons is that total RNA in the tube foot is much less abundant than that in the haemocyte and intestine [28]. According to the length distribution of small RNAs, over 84.4% of the sequenced read had the length of 21–23 nt, which is the typical size range of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate its molecular mechanism, a comparative proteomic analysis of the global protein expression changes was also investigated after 7 days of exposure at 25°C in our previous work, and 8 proteins involved into material and energy metabolism showed significantly differential expression profiles during this process . Chen et al (2013) found that some microRNAs like miR-92, miR-2004, miR-2010 and miR-22 were also significantly over-expressed in aestivated sea cucumber, indicating that miRNAs were involved into this global transcriptional depression. But how these molecules affect sea cucumber metabolites and modulate metabolic pathways are still not well documented.…”
Section: Introductionmentioning
confidence: 94%
“…The sea cucumber, Apostichopus japonicus , is a commercially important marine organism that is raised in aquaculture along the coasts of China and has recently become a good model organism for studies of aestivation among marine invertebrates (Chen & Storey, ; Chen, Zhang, Liu, & Storey, ; Chen, Zhu, & Storey, ). This species naturally enters aestivation when ambient seawater temperature rises above 25°C during the summer months and can remain in dormancy for over 100 days (Yang et al., ).…”
Section: Introductionmentioning
confidence: 99%